Accuracy of QuantiFERON SARS-CoV-2 research use only assay and characterization of the CD4+ and CD8+ T cell-SARS-CoV-2 response: comparison with a homemade interferon-γ release assay. (September 2022) - Aiello, Alessandra; Coppola, Andrea; Vanini, Valentina; Petrone, Linda; Cuzzi, Gilda; Salmi, Andrea; Altera, Anna Maria Gerarda; Tortorella, Carla; Gualano, Gina; Gasperini, Claudio; Scolieri, Palma; Beccacece, Alessia; et al.
Highlights: The QuantiFERON SARS-CoV-2 research use only assay response is mediated by CD4 + and CD8 + T cells. Immune response to the antigen (Ag)2 tube is more accurate than that to the Ag1 tube. Responses to QuantiFERON SARS-CoV-2 tubes are lower compared with a homemade test. The QuantiFERON SARS-CoV-2 difference in accuracy is likely because of the peptide composition. Abstract: Objectives: In this study, we aimed to characterize the SARS-CoV-2-specific T cell response detected by the QuantiFERON SARS-CoV-2 research use only assay in terms of accuracy and T cell subsets involved compared with a homemade interferon (IFN)-γ release assay (IGRA). Methods: We evaluated T cell response by the standardized QuantiFERON SARS-CoV-2 tubes (antigen [Ag]1 and Ag2) and a homemade IGRA quantifying IFN-γ response to SARS-CoV-2 spike peptides (homemade-IGRA-SPIKE test). We evaluated the T cell subsets mediating the specific response using flow cytometry. Results: We prospectively enrolled 66 individuals: COVID-19 or post-COVID-19 subjects and NO-COVID-19-vaccinated subjects, including healthy donors and immunocompromised subjects. The standardized kit detected 62.1% (41/66) of T cell responders. Ag2 tube showed a higher IFN-γ quantitative and qualitative response. Ag1 tube response was mainly mediated by CD4 + T cells; Ag2 tube response was mediated by CD4 + and CD8 + T cells. The homemade-IGRA-SPIKE test detected a higher number of responders (52/66, 78.8%) than the QuantiFERON SARS-CoV-2 assay ( P  = 0.056). The response was found in both T cell subsets, although a higher magnitude and response rate was observed in the CD4 + T cell subset. Conclusion: The QuantiFERON SARS-CoV-2 response is mediated by CD4 + and CD8 + T cells. A lower number of responders is found compared with the homemade-IGRA-SPIKE test, likely because of the different peptide composition.